(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
Concepts of multiple causation, autoclitics and edition help behavior analytic therapists to conduct functional evaluations and to intervene. In evaluating the therapist takes into account that verbalization of clients have multiple determination and pays attention to subtleties of autoclitics and editions. He uses autoclitics to promote a good therapeutic relationship, adherence to treatment and to teach the client to describe his behavior and its controlling variables. Metaphors, fantasies and allegories are possible interventions based on multiple causation notion. Therapists can provide supplementary stimulation to strengthen existing but weak responses. The logic of clinical work being different from experimental analysis of behavior and that different contingencies analysis may be appropriate are discussed.